ANALISIS PRODUCT PLACEMENT DAN BRAND AWARENESS PERMEN KOPIKO DALAM DRAMA KOREA BLIND: ANALISIS PRODUCT PLACEMENT DAN BRAND AWARENESS PERMEN KOPIKO DALAM DRAMA KOREA BLIND - Asri, Lc Hsia; Agung, Maulana; Djausal, Gita Paramita (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2023)
ABSTRACT Product placement in movies or dramas is shown as part of the storyline so that the audience can indirectly see the product, brand or logo that appears. The appearance of a product in a movie/drama is an effort to raise brand awareness, which is the ability of consumers to remember a brand in a certain category. This study aims to determine the product placement and brand awareness of Kopiko candy that appears in the Korean drama Blind. The method in this research uses descriptive qualitative research method. Based on the research results, it is known that Kopiko appeared in the Korean drama Blind 2 twice. This research shows that Blind drama involves visual dimension, auditory dimension and plot connection. Product placement becomes a means of communication between Kopiko and the audience by indirectly conveying messages. The indicators met on brand awareness are at the brand recall stage where consumers understand the category of Kopiko candy. The level of brand awareness owned by informants has reached the Top Of Mind level.